1.3.1 Information Flow, Team Coordination, and Shared Knowledge in Integrated Concurrent Engineering. Issue 1 (July 2014) - Avnet, Mark S.
Abstract Large‐scale systems engineering efforts involve complex interactions that must be managed throughout the entire life cycle. Prior research has analyzed the relationship between expected and actual communication in engineering design teams. This study builds on that previous research by incorporating the cognitive aspects of design into the analysis. Based on 10 design sessions of an Integrated Concurrent Engineering (ICE) environment, Design Structure Matrix (DSM) representations of expected and reported interactions are constructed and used to calculate a metric of team coordination called socio‐technical congruence (STC). By computing the correlation between STC and a previously developed metric of shared cognition in teams, a relationship is found between team coordination and change in shared knowledge. Based on these results, it is concluded that design team members learn the most when expected and reported interactions are aligned – that is, when the team follows a well‐defined process based on information flow in the technical design.